Pengaruh Metode Sosiodrama Terhadap Hasil Belajar Kognitif Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam - Maria, Anly; Ramdani, Dikri (STAI Al-Musaddadiyah Garut, 2023)
The ability of students to comprehend material is crucial as it supports other necessary skills they must acquire. However, in Class XI MIA MA An-Nashr, many students have yet to meet the required proficiency criteria. Therefore, a stimulus is needed to assist students in achieving the desired cognitive learning outcomes. The objective of this study is to determine the effect of using the sociodrama method on students' cognitive learning outcomes. The research employs an experimental method with a pretest-posttest control group design. Data were collected through questionnaires, observations, interviews, and documentation. The analysis reveals that the calculated t-value exceeds the critical t-value (t_calculated > t_critical), specifically 13.63 ≥ 1.685. Consequently, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This leads to the conclusion that the sociodrama method significantly impacts the cognitive learning outcomes of students in the subject of Islamic Cultural History. Keywords: Sociodrama Method, Cognitive Learning Outcomes